(untitled) (Journal of Economic Research & Business Administration, 2015)
Astable situation in the world market of power resources about all an accruing sharpness show inevitability of increase of power efficiency of the world economy shown, first of all, in the form of the initiative under power savings, and increase in a share of renewed sources in global manufacture of energy. In turn Kazakhstan shows the raised interest to this points in question. This article about present condition and features of use of renewed energy sources in Kazakhstan.